Functioning of the Education System and Efficiency of Investing in Human Capital on the Example of the Industrial Sector of Ukraine - Yevhen REVTIUK; Yuliia VORZHAKOVA (Communications of International Proceedings, 2020)
Success of an enterprise depends on its employees’ human capital. This article investigates the influence of employees’ education on their human capital formation. The relationship between the quality of education and employment opportunities for graduates is assessed by the number of the employees working in their field of studies. The following assumptions are being investigated: the quality of education affects the ability to utilize the acquired human capital in the labor market of Ukraine; easy access to higher education in Ukraine creates a surplus in the labor market of specialists; receiving education abroad is a competitive advantage in the labor market in Ukraine. The data from 481 respondents’ (age ranges 18-60 years old and working in industry) questionnaires has been analysed. Evidently, there is a strong link between the quality of education and the ability to use a person's human capital accumulated during their studies. There is no link between the availability of education, which leads to oversaturation of the labor market with professionals in certain fields and the possibility of using human capital. Nevertheless, there is a shortage of highly qualified specialists in engineering industries in Ukraine today. Similarly, there is a strong link between indicators that characterize the attractiveness of education abroad and the ability to use human capital accumulated during training, and the attractiveness of obtaining specific social capital, namely experience in foreign companies and relationships. This indicates that engineering education obtained in Ukrainian universities, according to respondents, is quite competitive with similar education abroad.
Keywords: Human Capital; Human Resources; Educational System; Industrial Sector of Ukraine.